The library of Eusebius of Caesarea - Carriker, Andrew. (Vigiliae Christianae, Supplements, 2003)
This volume reconstructs the contents of the library in Roman Palestine of Eusebius of Caesarea (ca. 265-339) by examining Eusebius' major works, the Ecclesiastical History , Chronicon , Preparation for the Gospel , and Life of Constantine . After surveying the history of the library from its origins as an ecclesiastical archive and its true foundation by Origen of Alexandria to its disappearance in the seventh century, it discusses how Eusebius used his sources and then examines what specific works were available in the library in chapters devoted to philosophical works, poetry and rhetoric, histories, Jewish and Christian works, and contemporary documents. The book ends with a useful list of the contents of the library.